Tobacco consuming in engineering careers: causes and effects - Pule, Victor; Villarreal Bolaños, Andrés; Valverde Toapanta, Anderson; Arciniega Hidrobo, Silvia (EASI: Engineering and Applied Sciences in Industry, 2023)
The aim of the current study is to identify the causes and consequences of tobacco smoking social problems in the lives of students in the first years of engineering at a public university. A total of 107 students were selected and non-probabilistic sampling tests were carried out. An analysis was carried out based on the responses collected from an anonymous survey, which revealed the causes and effects of tobacco use in students to reach a general conclusion with the results obtained, how harmful it is to mental and physical health.
Keywords: Smoking; Causes; Consequences; Mental; Physical; Health